When and Where Residential Racial Segregation Matters for the Black Self-employment Rate. Issue 4 (December 2021) - Bento, Asia
Scholars debate whether residential racial segregation associates positively, negatively, or at all with the Black self-employment rate in the United States. This study engages that debate using data from the Integrated Public Use Microdata Series (IPUMS) 1980, 1990, and 2000 5% sample and 2006–2010 American Community Survey (ACS) 5-year sample. Specifically, I investigate the county-level association between residential racial segregation and the Black self-employment rate, and whether this association varied by region in 1980, 1990, 2000, and 2010. Using fractional logit models and net of control variables, I find that residential racial segregation positively predicts Black self-employment in the South. Implications for understanding how time and region condition Black self-employment opportunities are discussed.